1954
DOI: 10.1021/ie50529a026
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Low Temperature Char by Partial Gasification

Abstract: A considerable amount of literature has developed on the desulfurization of coke by treatment with hydrogen, steam, and other gases.The published work has been concerned largely with the desulfurization of high temperature coke in contradistinction to the work recorded here on low temperature char.The previous investigators were chiefly interested in the development of procedures for desulfurizing hot coke before it was pushed from the oven. These procedures were empirical, and no systematic investigation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…This can be tested by using the following mass-transfer equation, assuming a negligible amount of H2S in the H2 stream. ~j q%s )e JH2S = D12 2r o RT [1] where JHzS ~ flux of HzS through the gas-film boundary, Dlz = interdiffusivity of H a-HzS , r o = average radius of the pyrrhotite spheroids, (p H2S) e = equilibrium partial pressure of H2S for the iron-pyrrhotite equilibrium at 1 arm Ha, R = gas constant, T = temperature, Nu = average Nusselt number.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be tested by using the following mass-transfer equation, assuming a negligible amount of H2S in the H2 stream. ~j q%s )e JH2S = D12 2r o RT [1] where JHzS ~ flux of HzS through the gas-film boundary, Dlz = interdiffusivity of H a-HzS , r o = average radius of the pyrrhotite spheroids, (p H2S) e = equilibrium partial pressure of H2S for the iron-pyrrhotite equilibrium at 1 arm Ha, R = gas constant, T = temperature, Nu = average Nusselt number.…”
Section: Resultsmentioning
confidence: 99%
“…7 The loss of sulfur calculated from Eq. [1], for masstransfer control, is shown by the broken lines in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal decomposition and secondary gasification reactions also lead to the formation of other sulfur gas species including carbonyl sulfide (COS), carbon disulfide, and various thiophenes and mercaptans. Studies of coal desulfurization chemistry have been reported by Zielke et al (1954) (1977), Huang and Pulsifer (1977), Attar (1978Attar ( , 1979, Torrest and VanMeurs (1980), and Yeboah et al (1982), and kinetic studies of H2S evolution have been performed for coal pyrolysis (Solomon, 1977;Lester et al, 1982;Attar and Messenger, 1983) and coal hydrogasification (Vestal et al, 1969(Vestal et al, ,b, 1972; ; Yergey et al, 1974).…”
mentioning
confidence: 99%
“…Unfortunately the hydrodesulfurization of coal is inhibited by hydrogen sulfide in the gas phase which severely limits the concentration build-up of hydrogen sulfide (5,8,9,10).…”
mentioning
confidence: 99%